Association of Hypertension and Coronary Heart Diseases (KYAMC Journal, 2021)
Background: Hypertension is one and the major non-transferable diseases in the world and contributing altogether to the burden of cardiovascular diseases, stroke, kidney failure, and premature death. The association of hypertension and coronary heart disease is a very frequent one. Just 11% of the total instances of hypertension have compelling control of circulatory strain.Objective: The main goal of this study is to assess the association between hypertension and coronary heart diseases.Materials and Methods:A prospective observational study was conducted in a total of 300 patients from January 2016 to July 2016 in a single institution (Private hospital) in Dhaka, Bangladesh. The incidence of hypertension, its control, and association with coronary heart diseases was analysed in the patients.Results: In our investigation, the outcomes demonstrated that hypertension is highly associated with cardiovascular diseases in patients above 50 years old (p=0.001). A total of 228 patients in the study had hypertension and 30 were recently recognized. 63% of the patients with hypertension have viable control of blood pressure with medications and systolic hypertension was revealed in 6% cases.Conclusion: Hypertension and its treatment are related to coronary heart diseases. Treatment should be meant to achieve optimal values of blood pressure, and all the methodologies to treat coronary heart diseases should be considered on an individual premise.KYAMC Journal.2021;12(1): 44-47